Analysis Of Village Government Transparency In Managing Village Funds In Telaga Dalam Village, Pino Raya District, South Bengkulu Regency - Wince Anisa Fitri; Wagini Wagini; Nenden Restu Hidayah (Penerbit Jurnal Indonesia, 2023)
The aim of the research is to find out how transparent the government is in managing Village Funds in Telaga Dalam Village, Pino Raya District, South Bengkulu Regency in 2022. This type of research uses descriptive qualitative research methods because the topic in this research is a topic that needs to be explored. Based on the results of the interviews presented in table 1, the transparency stage has been fully implemented in Telaga Dalam Village, Pinang Raya sub-district, South Bengkulu district and there is a notice board regarding the activities that will be carried out. Realization reports and APBD implementation reports have been informed to the public verbally and in writing and there is also media. information that is easily accessible to the public, such as notice boards, this is shown by a total of 100% answering accordingly. Based on Christian indicators regulated in Law No. 14 of 2008 and government regulation No. 60 of 2014, the government of Telaga Dalam Village, Pino Raya District, South Bengkulu Regency is transparent and in accordance with the legislation which is carried out with transparency by involving the community.